تحديد الاحتياجات التدريبية لمعلمات رياض الأطفال في ضوء تقويم الأداء من وجهة نظر مديرات الرياض في محافظتي اللاذقية وطرطوس - الجندي نزيه; علي وفيقه سليمان (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف البحث إلى تعرف الاحتياجات التدريبية لمعلمات رياض الأطفال في ضوء تقويم الأداء في محافظتي اللاذقية وطرطوس من وجهة نظر مديرات الرياض، وكذلك التعرف إلى الفروق في مستوى الأداء تبعاً للمتغيرات الآتية (عدد سنوات الخبرة، المؤهل العلمي). استخدم البحث المنهج الوصفي التحليلي، واشتملت العينة على (96) معلمة من معلمات رياض أطفال محافظتي اللاذقية وطرطوس للعام الدراسي 2011/2012. ولتحقيق هدف البحث صممت استبانة مكونة من أربعة مجالات احتوت (48) فقرة، تعبر عن أداء معلمات الرياض. أظهرت النتائج أن احتياجات معلمات رياض الأطفال جاءت بدرجة متوسطة في مجالات الاستبانة الأربع من وجهة نظر المديرات كما تبين وجود احتياجات تدريبية بدرجة مرتفعة بمجال تخطيط الدرس ومجال إدارة الصف ومجال الاتصال بأولياء الأمور في بعض محاور المجالات المذكورة. كما أظهرت النتائج وجود فروق دالة تبعاً لمتغير المؤهل العلمي بين المعلمات لصالح حملة الإجازة عند كل محور وعلى مستوى المحاور ككل، كما تبين وجود فروقٍ دالة تبعاً لمتغير الخبرة، إذ جاءت قيمة مستوى الدلالة أصغر من 0.05، عند درجات حرية (94) وبمستوى ثقة (5%) عند كل محور من محاور تقويم الأداء، وعلى مستوى المحاور كلها، لصالح عينة ذوي الخبرة (3 سنوات فأكثر)، بينما لم توجد فروق دالة جوهرياً عند محور الاتصال بأولياء الأمور، إذ جاءت قيمة مستوى الدلالة أكبر من 0.05، عند درجات حرية (94). قدم البحث مقترحات منها تدريب معلمات الرياض بناء على نتائج تقويم الأداء، وإجراء مزيد من البحوث المشابهة في محافظات القطر. This research aims to identify the training needs of kindergarten teachers in the light of performance evaluation in the provinces of Lattakia and Tartous from the viewpoint of Kindergartens principals, as well as to identify the differences in the level of performance according to two variables. The research has used the descriptive analytic method. The sample included (96) of female kindergarten teachers. To achieve the objective of this research a questionnaire of four areas has been designed. It included (48) paragraphs, which reflect the performance of kindergarten teachers. The results showed that the needs of kindergarten teachers were average needs in the four areas of the questionnaire from the perspective of female principals. The results have demonstrated highly-required training needs in the area of ​​lesson planning, classroom management and communication with parents in some of the themes of the previously mentioned topics. The results also showed the presence of statistically significant differences as to the variable of educational qualification among the teachers in favor of those who got a BA at each area separately and all of the areas together. On the other hand, there were no statistically significant differences regarding communication with parents. This research suggests training kindergartens teachers based on the results of performance evaluation, and conducting similar research papers all over the country.